In-situ Oxidation and Coupling of Anilines towards Unsymmetric Azobenzenes Using Flow Chemistry - Griwatz, Jan H.; Campi, Chiara E.; Kunz, Anne; Wegner, Hermann A.; Justus Liebig University Giessen (My University, 2024)
Molecular switches, especially azobenzenes, are used in numerous applications, such as molecular solar thermal storage (MOST) systems and photopharmacology. The Baeyer-Mills reaction of anilines and nitrosobenzenes has been established as an efficient synthetic method for non-symmetric azobenzenes. However, nitrosobenzenes are not stable, depending on their substitution pattern and pose a health risk. An in-situ oxidation of anilines with Oxone® was optimized under continuous flow conditions avoiding isolation and contact. The in-situ generated nitrosobenzene derivatives were subjected to a telescoped Baeyer-Mills reaction in flow. That way azobenzenes with a broad substituent spectrum were made accessible.
Keywords: ddc:540